TERAPI RUQYAH SYAR’IYYAH MENINGKATKAN KEBAHAGIAAN PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA - Arini Mifti Jayanti; Fuad Nashori; Rumiani Rumiani (JIP (Jurnal Intervensi Psikologi), 2019)
The purpose of this research is to explore ruqyah Syar’iyyah therapy effectiveness as a therapy to increase the happiness of domestic violence women. The assumption is the ruqyahsyar’iyyahbe able to increase the happiness. The subjects of the research are the age of on 18 years, who are victims of violence having average or low happiness scale. There scale used in the research is scale that arranged based on aspects of Seligman (2005). The data is analyzed by Mann Whitney. The results of the hypothesis done by using analysis Mann Whitney, obtained value U of 10.500 with p = 0.225 (p > 0.05) while on pascatest obtained by 0.000 with p = 0.004 (p<0.01). On a followup obtained value of 0.000 with p = 0.004 (p<0.01). The result of the hypothesis show that there is a difference level of happiness significant before and after given ruqyahsyar’iyyah therapy in of abused women.